7 - Philosophy and Development On the Problematic of African Development: A Diachronie Analysis: 10.4314/ad.v29i1.22189 - Keita, Lansana (Africa Development, 2004)
The idea of development is generally seen as central to any discussion of the economic, cultural, and political sociologies of the world's nations. Nations of the West are seen as 'developed' and members of the 'First World', while those of Africa, Latin America and some of those of Asia are seen as 'developing'and belonging to the 'Third World'. I propose to examine the meaning and application of the term 'development' with respect to Africa, then discuss whether Africa was ever developed—recognizing that the term is temporally relative. I will also discuss the idea of what Africa 'would look like' were it at the frontiers of development. I will then examine theories and applications of theories of development for Africa. Finally, I will examine current theories of development and their potential for success in Africa. Theories to be examined are the neoclassical theory, dependency theory, post-structuralism, and developmentalism.